CTLA-4 Blockade Plus Adoptive T-Cell Transfer Promotes Optimal Melanoma Immunity in Mice. Issue 2 (February 2015) - Mahvi, David A.; Meyers, Justin V.; Tatar, Andrew J.; Contreras, Amanda; Suresh, Marulasiddappa; Leverson, Glen E.; Sen, Siddhartha; Cho, Clifford S.
Abstract : Immunotherapeutic approaches to the treatment of advanced melanoma have relied on strategies that augment the responsiveness of endogenous tumor-specific T-cell populations [eg, cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) blockade-mediated checkpoint inhibition] or introduce exogenously prepared tumor-specific T-cell populations [eg, adoptive cell transfer (ACT)]. Although both approaches have shown considerable promise, response rates to these therapies remain suboptimal. We hypothesized that a combinatorial approach to immunotherapy using both CTLA-4 blockade and nonlymphodepletional ACT could offer additive therapeutic benefit. C57BL/6 mice were inoculated with syngeneic B16F10 melanoma tumors transfected to express low levels of the lymphocytic choriomeningitis virus peptide GP33 (B16GP33), and treated with no immunotherapy, CTLA-4 blockade, ACT, or combination immunotherapy of CTLA-4 blockade with ACT. Combination immunotherapy resulted in optimal control of B16GP33 melanoma tumors. Combination immunotherapy promoted a stronger local immune response reflected by enhanced tumor-infiltrating lymphocyte populations, and a stronger systemic immune responses reflected by more potent tumor antigen-specific T-cell activity in splenocytes. In addition, whereas both CTLA-4 blockade and combination immunotherapy were able to promote long-term immunity against B16GP33 tumors, only combination immunotherapy was capable of promoting immunity against parental B16F10 tumors as well. Our findings suggest that a combinatorial approach using CTLA-4 blockade with nonlymphodepletional ACT may promote additive endogenous and exogenous T-cell activities that enable greater therapeutic efficacy in the treatment of melanoma.